2019
DOI: 10.4103/sjg.sjg_455_18
|View full text |Cite
|
Sign up to set email alerts
|

The gap between knowledge and undergoing colorectal cancer screening using the Health Belief Model: A national survey

Abstract: Background/Aims:Colorectal cancer (CRC) is a public health issue, and before the initiation of a national cancer screening program, there is a need to examine the acceptance of the public to undergo CRC screening and explore potential barriers.Materials and Methods:A nationwide survey was conducted using an electronic platform to collect demographic variables and using the Health Belief Model to assess attitudes and behavior of participants as well as the knowledge about and intent to undergo CRC screening. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 42 publications
3
55
3
Order By: Relevance
“…However, it also needs to be noted that a review by Wools et al [7], including studies worldwide, found female gender rather to be a barrier than a facilitator, so ndings about gender might be country-speci c. The higher responsivity among older participants is in line with results from a 12-country study by Klabunde et al [6] as well as by a review by Wools et al [7] and might re ect a stronger awareness of older people about the fact that colon cancer risk increases with age and/or less restrictive time schedules among those who have left the labor market.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…However, it also needs to be noted that a review by Wools et al [7], including studies worldwide, found female gender rather to be a barrier than a facilitator, so ndings about gender might be country-speci c. The higher responsivity among older participants is in line with results from a 12-country study by Klabunde et al [6] as well as by a review by Wools et al [7] and might re ect a stronger awareness of older people about the fact that colon cancer risk increases with age and/or less restrictive time schedules among those who have left the labor market.…”
Section: Discussionsupporting
confidence: 64%
“…The difference to the 65,3% participation rate reported by a Danish registry study for 2015/2016 [16] can be explained by the different criterion of "ever-use" (at least once) employed in the present study. In comparison to other countries [6,7], Danes in general appear to have a high level of acceptance of the national colon cancer screening program. The overall high participation rate might be explained by a postal reminder which is sent every second year to non-participants.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Likewise, lifestyle behavior, health-related attitudes and cognitive styles seem to make a difference [4]. For health literacy, however, most studies failed to show an expected positive association with participation in screening for CRC [5,6], but methodological differences across studies in the assessment of health literacy challenge inter-study comparisons [5].…”
Section: Introductionmentioning
confidence: 99%
“…The Health Belief model method is a comprehensive model that can be used for organizing educations. The HBM is a number of the first models which were advanced for regulating health-related behaviors 8 . On this version there are specific patterns of social-cognitive predictors can also appear ( Figure 1) the construct of "Commitment to Plan of Action" from "Health Promotion Model Added to HBM model.…”
Section: Introductionmentioning
confidence: 99%